PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPETWO STAY TWO STRAY UNTUK MENINGKATKAN HASIL BELAJAR IPSKELAS IV SD NEGERI 010 SILIKUAN HULU - Edi Sutrisna (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study is the low learning outcomes IPS SD Negeri 010 Silikuan Hulu. It is characterized by the acquisition value of the average student at 64.34, besides completeness of student learning outcomes is only 40.63% or only 13 students out of 32 students. The low yield of this study was due to: (a) teachers do not master the subject matter; (B) teachers still use the lecture method; (C) teachers do not use instructional media; and (d) learning social studies focused only on teacher. The problems, researchers make improvements learning by doing classroom action research by applying cooperative learning model two stay two stray. This study was conducted by two cycles of each cycle to which it consists of two meetings and one daily tests. The data collection technique used is the technique oberservasi activities of students and teachers and achievement test. The results showed that the application of cooperative learning model two stay two stray can increasing the activity of teachers and students as well as students' learning outcomes IPS, it is supported by the following results: (a) an increase in activity of teachers and students of the first cycle and the second cycle. For the first cycle of teacher activity increased 61.60% to 81.25% cycled II with an increase of 19.65%. For students in the first cycle of activity 61.61% increase in cycle II to 82.14% with an increase of 20.53%; and (b) An increase in student learning outcomes in basic score with an average of 64.34. In the first cycle increased to 68.75 and the second cycle increased to 76.86.